ABUNDANCE AND DISTRIBUTION OF BLOOD CLAMS (Anadara granosa) IN COASTAL WATERS OF MEKARBARU VILLAGE KEPULAUAN MERANTI - Sulistio, Hendra Tri; Efriyeldi, Efriyeldi; Galib, Musrifin (Asian Journal of Aquatic Sciences, 2020)
This research is expected to find out how abundance and distribution of blood clams (Anadara Granosa) in coastal waters of Mekarbaru village, Kepulauan Meranti District. In good conditions or during the season in a particular month there is more capture compared to when it is not in season. Analyze using descriptive analysis research methods using survey methods. The materials used in this study were blood clam samples (A.granosa), and aquades for tool rinsing. The results of this study can be concluded that the average abundance of blood clams of A. granosa in the coastal waters of Mekarbaru Village, Kepulauan Meranti District is different. The highest average blood clam abundance was found at station III which was 21.86 Ind / m2 and the lowest was at station II which was 19.63 Ind/m2. The size distribution of blood clams A. granosa can be seen that dominating is the size of <25 mm (small), while the size of 25-30 mm (Medium) is only found at each station. The abundance of small blood clams A. granosa is influenced by the content of sediment organic matter and water quality in the coastal waters of Mekarbaru Village, Kepulauan Meranti Regency.